Pengaruh Social Support dan Social Comparison terhadap Self-Esteem pada Remaja Yatim Piatu di Panti Asuhan - Nurani, Mahatma Elok; Sanjaya, Ersa Lanang (Personifikasi: Jurnal Ilmu Psikologi, 2025)
During adolescence, seeking their identity is considered one of the crucial tasks in the developmental stage. It allows adolescents to experience an identity crisis if they lack positive self-esteem. Factors contributing to the formation of self-esteem, a characteristic synonymous with adolescence include social support from their parents and social comparison within their environment. However, not all adolescents can receive social support from their parents or families. This led to the present study aiming to investigate the influence of social support and social comparison on the self-esteem of orphaned adolescents residing in orphanages. Participants in this study were orphaned adolescents aged 13 to 17 years residing in orphanages. Purposive sampling was employed as the sampling technique, and multiple linear regression analysis using JASP software was utilized for data analysis. The results of the multiple linear regression analysis indicated that social support and social comparison significantly influence the self-esteem of orphaned adolescents, accounting for 57% of the variance. Additionally, the study examined the extent to which the social support variable influences self-esteem.